Perfection of mechanism of estimation and management labour potential in the conditions of adaptation to requirements of international integration - Dobykina, Y. (Економічний вісник Донбасу, 2016)
In this article it is accented that in the crisis of the world economy and, especially for countries with transformational nature of management, of particular relevance is optimal formation of such an element of the economic potential of the enterprise as the labour potential. This urgency is due to the fact that this factor is fundamental as a catalyst of such an intangible asset of the company as goodwill. The approaches of valuation of labour potential are considered. In order to improve the employment potential of the control system an analysis of the labour potential competitive space is proposed, that allows to evaluate systematically all its characteristics. The trajectory in the competitive space for the purpose of company goodwill formation and, finally, for the market value increase is suggested as well У статті акцентовано, що в кризових умовах світової економіки і, зокрема для країн з трансформаційним характером господарювання, особливу актуальність набуває оптимальне формування такого елементу економічного потенціалу підприємства як трудовий потенціал. Ця актуальність обумовлена ще і тим, що останній є основоположним чинником, свого роду каталізатором, такого нематеріального активу як гудвіл фірми. Розглянуто підходи вартісної оцінки трудового потенціалу. В цілях удосконалення системи управління трудовим потенціалом пропонується аналіз конкурентного простору трудового потенціалу, що дозволить системно оцінити всі його характеристики, і траєкторію руху в конкурентному просторі з метою формування гудвілу фірми і, зрештою, підвищення ринкової вартості. В статье акцентировано, что в кризисных условиях мировой экономики и, особенно для стран с трансформационным характером хозяйствования, особую актуальность приобретает оптимальное формирование такого элемента экономического потенциала предприятия как трудовой потенциал. Эта актуальность обусловлена еще и тем, что последний является основополагающим фактором, своего рода катализатором, такого нематериального актива как гудвилл фирмы. Рассмотрены подходы стоимостной оценки трудового потенциала. В целях совершенствования системы управления трудовым потенциалом предлагается анализ конкурентного пространства трудового потенциала, что позволит системно оценить все его характеристики, и траекторию движения в конкурентном пространстве с целью формирования гудвила фирмы и, в конечном итоге, повышения рыночной стоимости.